AIS Movement Science - Biomechanics, Performance Analysis and Skill Acquisition (2010)
The AIS Movement Science discipline was established on 1 July 2010 to develop an integrating approach to the observation and analysis of performance in training and competition environments. This approach draws upon the distinctiveness of disciplined Biomechanics` insights and the emerging methodologies and theoretical insights offered by Performance Analysis and Skill Acquisition.